PERAN INTENSITAS MORAL DALAM PROSES PENGAMBILAN KEPUTUSAN ETIS: KAJIAN LINTAS BUDAYA - Vemita - Sinantia (Universitas Negeri Makassar, 2018)
This cross cultural study has tried to correlate the influence of moral intensity on ethical decision making, for instance on the stage of moral awareness. The phenomenon is interesting to investigate more because there is a difference between individualism culture and collectivism culture in ethical decision making, especially in the correlation of moral intensity components that influence ethical decision making process (Heyler, Armenakis, Walker, & Collier, 2016; McMahon & Harvey, 2007; Saat, Yusoff, & Panatik, 2014; Singh, Vitell, Al-Khatib, & Clark, 2007). Planned behavior theory stated that an individu make a decision based on individual ability to control his or her decision, this theory has been applied in individualism culture (Ajzen, 1991). In other hand, collectivism culture has a different finding with planned behavior theory. An individu in collectivism culture tend to make a decision ethically based on social group control (Ashkanasy, Windsor, & Trevino, 2006; Saat et al., 2014). The different findings on both culture is interesting to discuss more, in order to understand how Indonesian employee as a collectivism culture, and to determine the right ethical training approach for them.